1996
DOI: 10.1074/jbc.271.27.16294
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Identification of -Acyl-D-glucosamine 2-Epimerase from Porcine Kidney as a Renin-binding Protein

Abstract: Chem. 265, 6556 -6561) (identity: 99.6% in nucleotide sequence, 99.0% in amino acid sequence). That GlcNAc 2-epimerase is a RnBP was confirmed by its ability to bind porcine kidney renin and mask its protease activity. These findings provide unequivocal evidence that the enzyme GlcNAc 2-epimerase is a RnBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 27 publications
(31 reference statements)
0
54
0
3
Order By: Relevance
“…In order to determine the length of incubation that would result in optimal conversion of radiolabeled substrates, a time course was performed using compound 9c ( Figure 6B). This experiment indicated that, at least for Ac 4 ManNAc, conversion of exogenous peracetylated substrate to cytosolic intermediates was optimal between 20 and 24 hours.…”
Section: Analysis Of Cytosolic Mannosamine Metabolites Using 14 C-ac mentioning
confidence: 95%
“…In order to determine the length of incubation that would result in optimal conversion of radiolabeled substrates, a time course was performed using compound 9c ( Figure 6B). This experiment indicated that, at least for Ac 4 ManNAc, conversion of exogenous peracetylated substrate to cytosolic intermediates was optimal between 20 and 24 hours.…”
Section: Analysis Of Cytosolic Mannosamine Metabolites Using 14 C-ac mentioning
confidence: 95%
“…We and others found that a prorenin binding protein exists on the surface of plasma membrane in humans (1)(2)(3)(4)(5) and in rat tissues (6) and that its binding to prorenin activates proenzyme by a conformational change without proteolytically cleaving the 43-amino acid prosegment off the main body of active (mature) renin. Because the prorenin receptor localizes to the kidney (4), the locally activated prorenin by prorenin receptor can generate angiotensin I (AngI) and II (AngII) locally and exert its local action, leading to renal damage.…”
mentioning
confidence: 99%
“…53) As for the = -barrel, we have confirmed that a porcine kidney bifunctional protein, renin-binding protein [N-acyl-D-glucosamine 2-epimerase (AGE)], 54,55) a novel glycosaminoglycan-degrading enzyme of unsaturated glucuronyl hydrolase (UGL) of Bacillus sp. GL1, 56,57) a plant cell wall-degrading enzyme (B. subtilis unsaturated galacturonyl hydrolase) YteR, 58) and an AGE structural homolog, YihS, (unpublished) of S. typhimurium have = -barrel structures as a basic scaffold.…”
Section: Structural Features Of Polysaccharide Lyasementioning
confidence: 65%